Problems of achieving systematic targets of the national project «Science» - A. N. Petrov; N. G. Kurakova (Ekonomika Nauki, 2019)
The research focus of the analysis was on targets and activities of the national project «Science», the totality of which, according to the research hypothesis, is devoid of systemic nature. The absence of sush a system creates risks of not achieving the national goal, formulated as «accelerating the technological development of the Russian Federation, increasing the number of organizations implementing technological innovations, to 50 percent of their total number». Examples of the lack of interconnectedness of the targets proposed in the passport, indicating the presence of non-harmonized and multidirectional strategic verticals of the national project «Science», are given.